Characterization, attributes and market potential of cocoa honey (Research, Society and Development, 2021)
Cocoa honey is a by-product of cocoa production and its volume has been increasing with the growth of chocolate and derivatives industry. This liquid produced naturally during cocoa post harvesting has bittersweet flavor and light color, presents bioactive compounds, sugars, vitamin C and dietary fibers, compounds of importance to the food industry. Its industrial application still requires in-depth studies and technological development; however, the literature already points to research for the development of new products containing cocoa honey such as ice cream, mixed jams, vinegars and alcoholic beverages. Currently the use of cocoa honey occurs in a timid, often artisanal way, limited to cocoa-producing properties due to restrictions on its industrial use and issues such as its conservation, which nowadays occurs basically by freezing process. With the need to strengthen the bioeconomy and make a sustainable use of the production chains, there is a great need to develop products from cocoa honey, in order to avoid its disposal and add income to producers. This review describes the obtaining, physical-chemical composition, bioactive and technological potential of cocoa honey, within the cocoa processing chain.